The Influence of Motivation and Work Environment on Teacher Performance in Elementary Schools in North Jakarta - Zaen, Farhan Az Zuhri; Fauzobihi, Fauzobihi; Taryanto, Taryanto (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The purpose of this study is to determine the effect of work motivation, on teacher performance, determine the influence of the work environment on teacher performance and determine the influence of work motivation and work environment together on teacher performance in elementary schools in North Jakarta. This study used quantitative descriptive methods with data collection techniques through the distribution of questionnaires. In this study using saturated sampling with a sample of 31 employees in North Jakarta Elementary School, using multiple linear regression data analysis techniques. The results of this study show that there is an influence of work motivation, on teacher performance, knowing the influence of the work environment on teacher performance and knowing the influence of work motivation and work environment together on teacher performance in elementary schools in North Jakarta. The variables of work motivation and work environment have a moderate influence and have a contribution of 76.2% influence on teacher performance variables. The results of this study are expected to contribute to future research.